Genetic diversity for resistance to Pseudomonas solanacearum in tomato : evaluation of a Central American tomato plant introduction collection (CATIE), and a comparison of resistant tomato cultivars as hybrid parents - González Ugalde, William Gerardo ([editor no identificado], 1993)
Tesis (Master of Science)--Iowa State University, 1993.